Cross-cultural adaptation and psychometric properties study of Prolonged Grief Disorder Questionnaire (PG-12-R) for caregivers of terminal cancer patients, Thai version - Apinya Sae-Lim; Chathaya Wongrathanandha; Thayakorn Kittichai; Arthit Chaithanasarn (PLoS ONE, 2026)
Objectives To translate, culturally adapt, and validate a Thai version of the Prolonged Grief Disorder Questionnaire (PG-12-R) for application with caregivers of terminal cancer patients. Methods This quantitative cross-sectional study was conducted in two phases. The translation and cultural adaptation processes were in accordance with established guidelines, which included forward translation, reconciliation, back translation, expert committee review, pilot testing with 30 caregivers, and finalization. The validation phase comprised 165 caregivers recruited from the palliative care service at Ramathibodi Hospital. Participants completed the Thai PG-12-R, Thai versions of the Generalized Anxiety Disorder–7 (GAD-7), the Patient Health Questionnaire–9 (PHQ-9), and the Short Form Zarit Burden Interview (ZBI). The test–retest reliability was assessed over a two-week interval. The psychometric evaluation included Cronbach’s alpha, intraclass correlation coefficients (ICC), content validity index (CVI), exploratory factor analysis (EFA), simple linear regression coefficient, and Spearman’s correlation coefficients. Results The Thai version of the PG-12-R demonstrated excellent content validity (scale-level CVI = 0.92). Face validity ensured that the scale was culturally adapted to Thai expressions of grief. Structural validity assessment using EFA supported a unidimensional model (excluding Item Q3 due to low factor loading), with the single factor accounting for 67.61% of the total variance (eigenvalue = 4.27). The scale showed good internal consistency (Cronbach’s alpha = 0.87) and test–retest reliability (ICC = 0.88). Convergent validity was established through significant positive correlations with depression (PHQ-9: Spearman’s ρ = 0.67), anxiety (GAD-7: ρ = 0.59), and caregiver burden (ZBI: ρ = 0.60). Simple linear regression analysis confirmed that scores on the PHQ-9 ( β = 1.11 ), GAD-7 ( β = 1.20 ), and ZBI ( β = 0.54 ) were all significant predictors of grief severity. Conclusions The modified Thai PG-12-R is a reliable and valid instrument for assessing anticipatory grief in caregivers of terminally ill cancer patients. Its conciseness and accessibility enable its application in conventional palliative care for early identification of high-risk caregivers and the development of specific interventions.